2009
DOI: 10.1007/s00210-009-0397-9
|View full text |Cite
|
Sign up to set email alerts
|

Lectin extracted from Canavalia grandiflora seeds presents potential anti-inflammatory and analgesic effects

Abstract: Neutrophil migration is responsible for tissue damage observed in inflammatory diseases and is also implicated in inflammatory nociception. The use of lectins has been demonstrated to be effective in different activities including anti-inflammatory, antimicrobial, and in cancer therapy. In this study, we addressed the potential use of a lectin from Canavalia grandiflora seeds (ConGF) to control neutrophil migration and inflammatory hypernociception. Pretreatment of the animals intravenously (15 min before) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…Among them, ConM is the different one in oedema induction without NO participation, lower antinociceptive efficacy or higher efficacy and potency in vasorelaxant action. Similar to ConM, Canavalia grandiflora lectin acts as anti-inflammatory and analgesic [58] and has an oedematogenic activity in rat paw oedema model (s.c.), but has a vasorelaxant effect in endothelized rat aorta [59].…”
Section: Resultsmentioning
confidence: 99%
“…Among them, ConM is the different one in oedema induction without NO participation, lower antinociceptive efficacy or higher efficacy and potency in vasorelaxant action. Similar to ConM, Canavalia grandiflora lectin acts as anti-inflammatory and analgesic [58] and has an oedematogenic activity in rat paw oedema model (s.c.), but has a vasorelaxant effect in endothelized rat aorta [59].…”
Section: Resultsmentioning
confidence: 99%
“…More than a century later, numerous publications still report diverse biological events of pharmacological, immunological, or toxicological origin displayed by exogenous lectins on cell systems, or in in vivo studies [1,2]. As one example from such diversity, many plant lectins induce changes in the course of inflammatory processes in acute inflammation models [3]. Frequently, previous incubation of a lectin with the specific carbohydrate inhibitor of its hemagglutinating activity rendered the lectin unable to provoke any effect, thus confirming the involvement of the carbohydrate-binding domain in mediating the biological effect studied [4].…”
Section: Introductionmentioning
confidence: 99%
“…As shown by Rivanor et al, 2014 [11], who demonstrated the anti-nociceptive and anti-inflammatory efficacy of a lectin from the green seaweed Caulerpa cupressoides (CcL) in a model of zymosan-induced TMJ inflammatory hypernociception in rats, our study strongly suggest that the efficacy of AEL, similarly to CcL, involves inhibition of TNF-α and IL-1β production. Others authors have demonstrated antiinflammatory effects of lectins, showing dependence on TNF-α and IL-1β inhibition in classical models of nociception and acute inflammation in vivo [25][26][27][28][29]. The resolution of the inflammatory response during inflammatory hyper-nociception might be attributed to the inhibition of pro-inflammatory cytokines, such TNF-α and IL-1β.…”
Section: Discussionmentioning
confidence: 97%